Comparison of Sharia Stock Prices and Trading Volumes Before and During COVID-19 - Ameliana Yunus, Yana (Golden Ratio of Finance Management, 2021)
Before making an investment, entrepreneurs or investors must consider the benefits and financial risks obtained. So, investors need to take action in investing, meaning that investors need to form a portfolio by selecting several assets so that financial risk can be minimized without reducing the expected. The COVID-19 pandemic has significantly impacted the economy, especially investors, informing an optimal portfolio. This study aims to determine the optimal portfolio formation during the COVID-19 pandemic. In this study measurement, we used variables in the form of stock prices and stock trading volumes before and during COVID-19 pandemic. This study shows a comparison, but not so significant, between stock prices before and during the pandemic. Based on the survey conducted, the following results were found, i.e., first, shows an insignificant difference between prices before and after the rights issue announcement. The stock trading volume indicates a significant difference between the stock trading volume before and after the rights issue; trading volume increases after the information of the rights issue. By implementing companies affected by COVID-19 pandemic, we can watch the prices that occur around the announcement date. Investors can make a reason about their investments in shares of issuers affected by COVID-19 pandemic.